Iron‐Catalyzed Oxidative C−C and N−N Coupling of Diarylamines and Synthesis of Spiroacridines1. Issue 2 (5th December 2016) - Fritsche, Raphael F.; Theumer, Gabriele; Kataeva, Olga; Knölker, Hans‐Joachim
Abstract: We describe iron‐catalyzed intermolecular oxidative coupling reactions of diarylamines to form substituted 2, 2′‐bis(arylamino)biaryl compounds, tetraarylhydrazines, and 5, 6‐dihydrobenzo[ c ]cinnolines with the same hexadecafluorinated iron–phthalocyanine catalyst. The mild formation of C−C or N−N bonds was controlled by the use of acidic or basic additives. In contrast to most iron‐catalyzed dehydrogenative coupling reactions, ambient air could be used as the sole oxidant. Moreover, iron(III) chloride hexahydrate promoted a one‐pot coupling and subsequent intramolecular dearomative coupling to give 10 H ‐spiro[acridine‐9, 1′‐cyclohexa‐2′, 5′‐dien‐4′‐ones]. Abstract : Let us count the ways… Catalysis by iron–hexadecafluorophthalocyanine enabled the aerobic coupling of diarylamines to form 2, 2′‐bis(arylamino)biaryl compounds, tetraarylhydrazines, or 5, 6‐dihydrobenzo[ c ]cinnolines. The chemoselectivity of these transformations was controlled by acid or base additives (see picture).